Prevalence and Incidence of Hypertension in the General Adult Population: Results of the CARLA-Cohort Study - Lacruz, Maria E.; Kluttig, Alexander; Hartwig, Saskia; Löer, Markus; Tiller, Daniel; Greiser, Karin H.; Werdan, Karl; Haerting, Johannes (Medicine (Baltimore), 2015)
Hypertension is a leading cause of cardiovascular disease. There are very few studies dealing with the incidence of hypertension and changes in blood pressure (BP) over time. We aimed to evaluate the prevalence and incidence of hypertension within an adult population-based cohort.The sample included 967 men and 812 women aged 45 to 83 years at baseline, 1436 subjects completed follow-up1 after 4 years and 1079 completed follow-up2 after 9 years. BP was measured according to a standardized protocol with oscillometric devices and hypertension was defined as mean systolic BP (SBP) ≥140  mmHg and/or diastolic BP (DBP) ≥90  mmHg and/or use of antihypertensive medication if hypertension was known. We examined prevalence and incidence of hypertension, by age and sex.The age-standardized prevalence of hypertension at baseline was 74.3% for men and 70.2% for women. The age-standardized annual incidence rate of hypertension for men was 8.6 (95% confidence interval [95% CI] 4.3-12.9) for follow-up period1 and 5.4 (95% CI 2.8-10.6) for follow-up period2 and for women 8.2 (95% CI 3.6-12.8) for follow-up1 and 5.6 (95%CI 2.7-11.4) for follow-up2. A clear decrease in SBP and DBP between baseline and follow-up1 and follow-up2 was seen, accompanied by an increase in anti-hypertensive medication consumption and a higher awareness of the condition.Hypertension prevalence and incidence in the CARLA Study appear to be elevated compared with other studies. The decrease of BP over time seems to be caused by improved hypertension control due to interventional effects of our observational study and improved health care.